Identity-based proxy re-encryption with equality test - Santos, Diogo Pereira da Silva (2020)
Identity-Based Encryption (IBE) is a powerful cryptographic primitive, where users’ public key can be derived from unique information representing their identity such as their email address. Unlike traditional public key cryptography schemes, IBE does not require the use of digital certificates nor certified authorities in its implementation. Identity-based proxy re-encryption allows an authorized user to encrypt the ciphertext under Alice’s identity into another ciphertext from the same message under Bob’s identity. The authorized user is known as proxy, and an identity is itself a public key. Therefore, Identity-based Proxy Re-encryption is an ideal primitive for data sharing in cloud computing, because, even if data stored in the cloud is encrypted, a user can securely share it with other users without a fully trusted cloud server. Identity-based Encryption with Equality Test is a cryptographic primitive that allows a third party in possession of a trapdoor performs equality tests between ciphertexts encrypted by the same identity and between ciphertext encrypted by different identities. This primitive has many practical applications, such as search on encrypted data. This dissertation presents a new and innovative Lattice-based Identity-based Proxy Re-encryption with Equality Test. Lattice-based cryptography is one of the important topics in cryptography because it a post-quantum cryptography algorithm, i.e., it is believed to be safe against attacks with quantum computers. In addition, lattice cryptography is asymptotically fast since its algorithms involve only linear algebraic operations. This dissertation presents a comparison between the proposed scheme and similar schemes, both in the communication cost and in the computational cost.